ELECTRONIC AND GEOMETRIC STRUCTURE OF ADSORBATES ON OXIDE SURFACES - Libuda, Jörg; et al. (ELSEVIER SCIENCE BV, 1994)
We have investigated the electronic and geometric structure of surfaces of transition metal oxides and simple metal oxides applying electron spectroscopic methods. In order to avoid charging problems, we have resorted to the preparation of thin (5 - 50 angstrom) metal oxide films grown on metallic substrates via several oxidation techniques. We have studied NiO, CoO, Cr2O3, and Al2O3. The thin films have the advantage that they may be easily cooled to liquid nitrogen and liquid helium temperatures. Another interesting feature of the thin films is the possibility to prepare thermodynamically unstable surfaces, such as (111) surfaces of ionic rock salt structures, and study the adsorption and reaction at such surfaces. Adsorption and reaction of molecules has not only been investigated on the clean oxide substrates but also on the surfaces modified through deposited ultrathin metal films. Such systems may be considered as models for heterogeneous catalysts.